Melampaui Digitalisasi: Dampak Holistik Penggunaan Teknologi Informasi dan Komunikasi dalam Dunia Pendidikan - Lutfiah, Izmi; Padli Nasution, Muhammad Irwan; Nasution, Wahyudin Nur (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the holistic impact of the use of Information and Communication Technology (ICT) in education, both from the positive and negative sides. With a qualitative approach and library study method, this study examines various literature and the latest research results related to the integration of ICT in learning. The results of the study show that the use of ICT makes a major contribution to increasing the effectiveness of learning, encouraging creativity, independence, and critical thinking skills of students. Various technology-based learning models have been proven to enrich teaching methods and expand access to information. However, on the other hand, challenges such as inequality in digital access, misuse of technology, and threats to moral and social values ​​are also impacts that need to be anticipated. Therefore, the use of ICT in education must be carried out wisely, structured, and accompanied by increasing digital competence for educators in order to support the improvement of the quality of education as a whole in the digital era.